Panretinal photocoagulation versus PRP plus intravitreal bevacizumab for high-risk proliferative diabetic retinopathy (IBeHi study) - Tonello, Matheus (2008)
Purpose: To evaluate the effects of panretinal photocoagulation (PRP) compared with PRP plus intravitreal bevacizumab on best corrected visual acuity (BCVA) and total area of fluorescein leakage from active new vessels (NVs) in patients with high-risk proliferative diabetic retinopathy (PDR).Methods: We carried out a prospective study of patients with high-risk PDR and no prior laser treatment who were randomly assigned to receive PRP (PRP group) or PRP plus intravitreal injection of 1.5 mg of bevacizumab (PRP-plus group). In all patients, the PRP was administered at two time-points (weeks 1 and 3), with the intravitreal bevacizumab delivered at the end of the second laser episode in the PRP-plus group. Standardized ophthalmic evaluation including Early Treatment Diabetic Retinopathy Study BCVA as well as stereoscopic fundus photography and fluorescein angiography were performed at baseline and at weeks 4, 9 (+/- 1) and 16 (+/- 2). Main outcome measures included changes in BCVA and in total area of fluorescein leakage from active NVs.Results: Twenty-two (n = 30 eyes) consecutive patients completed the 16-week follow-up. There was no significant difference between the PRP and PRP-plus groups with respect to age, gender, type or duration of diabetes, area of fluorescein leakage from active NVs or BCVA. No significant difference in BCVA was observed between the groups throughout the study period. However, the total area of actively leaking NVs was significantly reduced in the PRP-plus group compared with the PRP group at weeks 4, 9 and 16 (p < 0.001). No major adverse events were identified.Conclusions: In the short-term, the adjunctive use of intravitreal bevacizumab with PRP was associated with a greater reduction in the area of active leaking NVs than PRP alone in patients with high-risk PDR.